Maximizing benefits to bat populations through management of power line corridors - C. J. Campbell; Tina L. Cheng; Karin L. Akre; Amanda M. Adams; Donald I. Solick; Ashley Bennett; Christian Newman; Winifred F. Frick (Ecological Solutions and Evidence)
Abstract Power line corridors are ubiquitous worldwide and are commonly used by bats as habitat. Targeted management of these corridor habitats has the potential to aid bat populations, which is critically important given the multifaceted threats facing bat species, including the emerging infectious disease white‐nose syndrome (WNS) in North America. Here, we review known and potential impacts of management of existing power line corridors on three bat behaviours: foraging, roosting and commuting. We also identify bats in the United States that would benefit from changes to management of power line corridors for improvements to roosting and foraging habitats, particularly species of conservation concern that roost and forage along forest edges. Key recommendations are to avoid disturbance to roosting bats when maintaining vegetation along power line corridors, apply integrated vegetation management to maximize native plant diversity to improve prey options for bats and apply targeted interventions (e.g. artificial roost creation, creation of ponds) in a well‐justified ecological context. Practical implication. We highlight high‐priority research topics to fill knowledge gaps, including testing whether vegetation management treatments targeting plant and insect communities increase bat fitness and cause positive population‐level responses in focal bat species. We conclude that building evidence on how bats are affected by power line corridor management is a conservation need.